Smoking Cessation: A Review - Indi Esha; Riska Yuliana Sari (Respiratory Science, 2023)
Smoking is a leading cause of preventable death worldwide. Smoking damages almost all organs and body systems and reduces the overall health of a person with the highest mortality, especially due to respiratory and cardiovascular disease. Evidence shows that the symptoms and prognosis of smoking-related diseases will improve after smoking cessation. Smoking cessation is one of the most important ways to improve the prognosis of patients with respiratory ailments. Counseling and treatment can increase the chances of smokers to successfully smoke cessation. Smoking cessation therapy must include pharmacological treatment (Nicotine Replacement Therapy (NRT), bupropion, varenicline or N-acetylcysteine) combined with nonpharmacological therapy.